2020
DOI: 10.1002/mc.23269
|View full text |Cite
|
Sign up to set email alerts
|

p21‐activated kinase 4 promotes the progression of esophageal squamous cell carcinoma by targeting LASP1

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignant tumors of the digestive tract in humans. Several studies have indicated that PAK4 is associated with the risk of ESCC and may be a potential druggable kinase for ESCC treatment. However, the underlying mechanism remains largely unknown. The aim of our study is to identify the functional role of PAK4 in ESCC. To determine the expression of PAK4 in ESCC, Western blot analysis and immunohistochemistry were performed, and the results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…HSNCC is highly infiltrated by immune cells, including tumor-infiltrating lymphocytes (TILs) and myeloid lineage cells 11 , 12 . In the TME of HNSCC, tumor cells reportedly orchestrate a highly immunosuppressive state by secreting immunosuppressive mediators, expressing immune checkpoint ligands, and downregulating human leukocyte antigen expression 13 , 14 . These tumor cell behaviors result in the dysfunction and exhaustion of cytotoxic T lymphocytes (CTLs), as well as increased infiltration and activation of immunosuppressive cell types, such as regulatory T cells (Tregs), tumor-associated macrophages, and myeloid-derived suppressor cells (MDSCs) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…HSNCC is highly infiltrated by immune cells, including tumor-infiltrating lymphocytes (TILs) and myeloid lineage cells 11 , 12 . In the TME of HNSCC, tumor cells reportedly orchestrate a highly immunosuppressive state by secreting immunosuppressive mediators, expressing immune checkpoint ligands, and downregulating human leukocyte antigen expression 13 , 14 . These tumor cell behaviors result in the dysfunction and exhaustion of cytotoxic T lymphocytes (CTLs), as well as increased infiltration and activation of immunosuppressive cell types, such as regulatory T cells (Tregs), tumor-associated macrophages, and myeloid-derived suppressor cells (MDSCs) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the survival benefit is limited to only 20–30% patients, and new biomarkers that predict the efficacy of anti-PD-1 therapy have been investigated. Accumulating evidence has indicated that in HNSCC, tumor cells orchestrate a highly immunosuppressive tumor microenvironment (TME) via the production of immunosuppressive mediators, recruitment of various stromal cells, expression of immune checkpoint ligands, and downregulation of human leukocyte antigen expression 7 , 8 , which is referred to as immune evasion 9 . As immune checkpoint inhibitors, including anti-PD-1 antibodies, target the interaction between tumor cells and T cells, a comprehensive understanding of complex immune networks in the TME is needed to establish a new biomarker for immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…In cellular experiments, miR-206 inhibited the proliferation, migration and invasion of the HUCCT1 and RBE cell lines. LASP1 (LIM and SH3 domain protein 1) was recently identified as a regulator of tumor progression and drug resistance in several cancers, including CCA [25][26][27][28]. In this study, LASP1 was proven to be a target of miR-206 and promoted Nanog and TGF-beta1 expression via the STAT3 pathway.…”
Section: Discussionmentioning
confidence: 74%